THE INFLUENCE FACTORS OF GOVERNMENT SUPPORT, POLITICAL CONDITIONS, AND BUSINESS COMPETITION ON THE PERFORMANCE OF CONSTRUCTION SERVICES COMPANY PT. WIJAYA KARYA (Persero) Tbk - Apriyanto, Dwi (JRMSI - Jurnal Riset Manajemen Sains Indonesia, 2016)
The objective research is to obtain information on the effect of government support, political conditions and business competition in order to improve the performance of construction services company. Survey research methodology used survey. Data collection done toward 133 respondents. Respondent were chosen by simple random sampling technique. The data were collected with questionnaire and analysis with multiple regression. The results of the analysis concluded that the government support, political conditions and business competition have influence by direct or indirect on the performance of construction services company. The hypothesis is proven by indicators of significance of the influence between variable that more than (<) Î± = 0,05 and also the result of T-test that T count more than (>) T table., the most dominant variable is political conditions in influencing the performance of construction services company with significance value of 0.000. Keywords : Government support, Political condition, Business competition, and Performance of the company.